Web System of Announcement for School in Libya (WS_SL) - Elwahid, Ahmad Abubaker Abd (2009)
Web technology enables people to access digital information located in the Internet or also beyond the reach of stationary Internet access. The focus of this project is to apply Web-application field, particularly in observing schools' announcement in schools by school staff and ministry staff of the schools, the prospective system will facilitate to ministry staff to make announcements in the class and save it in the database of the school, the administrator also can add record of announcement, and the all of them school staff, ministry staff can oversee their announcement during school days. To achieve this goal, the study will adopt Object oriented development life cycle as a methodology, the four phases will be discussed in section of Research Methodology. Usability testing will be conducted to examine user's satisfaction, lastly to document the models of prototype.